Plant growth-promoting rhizobacteria inoculation to enhance vegetative growth, nitrogen fixation and nitrogen remobilisation of maize under greenhouse conditions - Kuan, Khing Boon; Othman, Radziah; Abdul Rahim, Khairuddin; Shamsuddin, Zulkifli (Public Library of Science, 2016)
Plant growth-promoting rhizobacteria (PGPR) may provide a biological alternative to fix atmospheric N2 and delay N remobilisation in maize plant to increase crop yield, based on an understanding that plant-N remobilisation is directly correlated to its plant senescence. Thus, four PGPR strains were selected from a series of bacterial strains isolated from maize roots at two locations in Malaysia. The PGPR strains were screened in vitro for their biochemical plant growth-promoting (PGP) abilities and plant growth promotion assays. These strains were identified as Klebsiella sp. Br1, Klebsiella pneumoniae Fr1, Bacillus pumilus S1r1 and Acinetobacter sp. S3r2 and a reference strain used was Bacillus subtilis UPMB10. All the PGPR strains were tested positive for N2 fixation, phosphate solubilisation and auxin production by in vitro tests. In a greenhouse experiment with reduced fertiliser-N input (a third of recommended fertiliser-N rate), the N2 fixation abilities of PGPR in association with maize were determined by 15N isotope dilution technique at two harvests, namely, prior to anthesis (D50) and ear harvest (D65). The results indicated that dry biomass of top, root and ear, total N content and bacterial colonisations in non-rhizosphere, rhizosphere and endosphere of maize roots were influenced by PGPR inoculation. In particular, the plants inoculated with B. pumilus S1r1 generally outperformed those with the other treatments. They produced the highest N2 fixing capacity of 30.5% (262 mg N2 fixed plant−1) and 25.5% (304 mg N2 fixed plant−1) of the total N requirement of maize top at D50 and D65, respectively. N remobilisation and plant senescence in maize were delayed by PGPR inoculation, which is an indicative of greater grain production. This is indicated by significant interactions between PGPR strains and time of harvests for parameters on N uptake and at. % 15Ne of tassel. The phenomenon is also supported by the lower N content in tassels of maize treated with PGPR, namely, B. pumilus S1r1, K. pneumoniae Fr1, B. subtilis UPMB10 and Acinetobacter sp. S3r2 at D65 harvest. This study provides evidence that PGPR inoculation, namely, B. pumilus S1r1 can biologically fix atmospheric N2 and provide an alternative technique, besides plant breeding, to delay N remobilisation in maize plant for higher ear yield (up to 30.9%) with reduced fertiliser-N input.